FEATURES OF THE CARDIOVERSION IN ATRIAL FLUTTER AND FIBRILLATION IN ERA OF NEW ANTICOAGULANTS: PRACTICAL CARDIOLOGIST VIEW - S. A. Zenin; A. V. Fedoseenko; O. V. Kononenko; O. V. Pyataeva (Рациональная фармакотерапия в кардиологии)
Strategies for the management of patients with atrial fibrillation (heart rhythm or heart rate control) are considered. The advantages of these methods, especially the implementation are presented. Based on their own data, authors give an algorithm to select the management strategy in particular patient. Preparation and implementation of electrical cardioversion procedure are described. The evidence base and analysis of complications of different anticoagulants use for safety of sinus rhythm restoration are presented.